BIM: the mapping of the QS’s role in contract administration - Abdullah Habib, Siti Nora Haryati (2018)
A Quantity Surveyor (QS) in the construction industry is known as the professional who possess expert knowledge in construction costs and contracts; and offers expert advice in regard thereto. As part of the team of professional advisors, their roles are vital in making sure that the resources are utilized at best efficiently possible simultaneously with preserving good contractual relationships among the project team members and the client. The arrival of Building Information Modelling (BIM) in the construction industry is a new challenge to the profession as it requires changes in the way the professional services are provided by a QS in order to accommodate collaborative and integrative environment that encouraged by the implementation of BIM. Most studies on the impact of BIM towards the QS profession have focused on the building measurement and costing aspects, but rarely touched on how QS’s functions in the area of contract administration are affected by BIM. Therefore, this paper is to highlight the BIM contractual challenges that need to be aware by QSs and opportunities that can be gained from BIM in order for QS to efficiently assist in administering construction contract. This study is considered significant as the knowledge may assist in developing strategies for QS professional development as well as updating the education and training needed for QS to cater BIM requirements.